2023
DOI: 10.1057/s41599-022-01482-0
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics, likelihood and challenges of road traffic injuries in China before COVID-19 and in the postpandemic era

Abstract: Through a review of previous studies, this paper analysed the epidemiological characteristics and attempts to determine the various trends of road traffic injuries (RTIs) in China before and after the coronavirus disease 2019 (COVID-19). This paper proposed effective measures and suggestions for responding to RTIs in China. Moreover, this paper aimed to provide some references for studies on RTIs in the future. According to a reference review, 50 articles related to RTIs were published and viewed in the China … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 46 publications
0
5
0
3
Order By: Relevance
“… 29 Although RTIs in China have also declined, the number of RTIs of e-bikes has increased despite strict control of public transportation. 30 There is no obvious downward trend of RTIs in Guangzhou in 2020 and 2021, which indicates that the road safety problem in Guangzhou is still serious.…”
Section: Discussionmentioning
confidence: 99%
“… 29 Although RTIs in China have also declined, the number of RTIs of e-bikes has increased despite strict control of public transportation. 30 There is no obvious downward trend of RTIs in Guangzhou in 2020 and 2021, which indicates that the road safety problem in Guangzhou is still serious.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, although some studies have reported that RTIs showed a downward trend attributed to road safety laws and various policies in China, the mortality of RTIs is still much higher than that in developed countries ( 9–11 ). As a result, it is still a very serious problem in China that should be paid more attention to ( 2 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…The direct economic loss caused by these accidents was RMB 243.63 billion, as reported in the 2019 Annual Report on Road Traffic Safety in China by the Institute of Highway Science of the Ministry of Transport of China. According to the global burden of disease research data, China accounted for 21% of global road traffic fatalities in 2017, equivalent to 0.6% of GDP [ 8 ].…”
Section: Introductionmentioning
confidence: 99%